The influence of inspiratory muscle training on lung function in female basketball players: a randomized controlled trial - Vasconcelos, Tiago (2017)
Inspiratory muscle fatigue may inhibit healthy athletes to achieve maximum performance, compromising blood flow and perfusion on locomotor muscles. Recent studies have showed irregular influence of inspiratory muscle training (IMT) on resting lung function. It was hypothesized that a 4-week IMT protocol would improve pulmonary function of basketball players. Twenty-one female basketball players were randomly assigned to an experimental group (EG) (n = 11) or a control group (CG) (n = 10). Pre- and post-forced expiratory volume in first second (FEV1), forced vital capacity (FVC) and peak expiratory flow (PEF) were assessed with spirometry in the beginning of the sport's season, at the first day of protocol and four weeks after. The EG (22.00 ± 5.00 years) was submitted to IMT using a threshold, 5 times a week, for a 4-week protocol (30 maximal repetitions (RM) against a pressure threshold load equivalent to 50% of maximal inspiratory pressure), while the CG (18.50 ± 5.75 years) was not subjected to any intervention during the same period. Baseline sociodemographic and anthropometric characteristics were not significantly different with the exception of age (p = 0.036). No significant differences were found in baseline pulmonary volumes (0.173 ≤ p ≤ 0.848) neither in predicted pulmonary variables (0.223 ≤ p ≤ 0.654). Significant increase on FEV1, FVC and PEF was found in the EG post-protocol (p < 0.001). In the CG, an improvement of PEF was found (p = 0.042). This type of specific inspiratory training appears to improve pulmonary function. Results suggest that the applied IMT protocol is effective. Further research is needed to assess the sustainability of the findings and to conclude the short and long term effects of IMT on basketball players.